2018
DOI: 10.21767/2049-5471.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sarcopenia and Sarcopenic Obesity Vary with Race/Ethnicity and Advancing Age

Abstract: Sarcopenia is the natural age-associated loss of muscle mass/function, often occurring simultaneously with obesity, especially in older adults. Sarcopenia and obesity contribute to poor health outcomes and when occurring together as sarcopenic obesity (SO) can cause further health complications. Few studies have specifically considered these conditions across different racial/ethnic populations. This study examined the prevalence of sarcopenia and SO among U.S. adults by different age, sex, and racial/ethnic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 47 publications
1
40
2
Order By: Relevance
“…Notably, the prevalence of sarcopenia among PLHIV in our study was also greater than observed in many chronic illnesses such as type 2 diabetes mellitus (ranged from 14.8 to 15.2%, aged >60 years) [14,49], chronic kidney disease (5.9%, aged 59.9 ± 10.5 years) [50], chronic obstructive pulmonary disease (14.5%, aged 63-73 years) [51], and obesity (5.5% in the 40-64 age group) [52]. In contrast, the sarcopenia prevalence among PLHIV was considerably lower than other conditions such as cirrhosis (48.1%) [53] or lung cancer (71%) [13].…”
Section: Plhiv Have Elevated Sarcopenia Prevalencecontrasting
confidence: 42%
“…Notably, the prevalence of sarcopenia among PLHIV in our study was also greater than observed in many chronic illnesses such as type 2 diabetes mellitus (ranged from 14.8 to 15.2%, aged >60 years) [14,49], chronic kidney disease (5.9%, aged 59.9 ± 10.5 years) [50], chronic obstructive pulmonary disease (14.5%, aged 63-73 years) [51], and obesity (5.5% in the 40-64 age group) [52]. In contrast, the sarcopenia prevalence among PLHIV was considerably lower than other conditions such as cirrhosis (48.1%) [53] or lung cancer (71%) [13].…”
Section: Plhiv Have Elevated Sarcopenia Prevalencecontrasting
confidence: 42%
“…Neither of our two females met the criteria which could indicate that the presence of sarcopenic obesity in different forms of muscular dystrophy is not equivocal. Notably, in adults without muscular dystrophy, it has been shown that females may be less, more, or as likely to develop sarcopenic obesity, as their male counterparts ( Du et al, 2018 ). Among whites, which formed the majority of our study (85%), rates of sarcopenic obesity are similar between age-matched males and females ( Du et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that in Brazil the classification of ethnicity is a challenge due to the high miscegenation (34) . Although the parameters used to define sarcopenia may present considerable variation depending on the ethnic groups and different geographic locations (14)(15)(16) , the three consensuses used in the present study to define sarcopenia are applicable in our sample population, considering that the proposed cutoff values were based on studies conducted in different ethnic groups and geographic locations (1,6,9) . The existing data regarding body composition, lifestyle and physical activities, factors that may affect the parameters used to define sarcopenia, are scarce among the populations of South America.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sarcopenia prevalence varies widely depending on the criteria used. Additionally, body composition variables including muscle mass, and muscle function parameters used for sarcopenia diagnosis, may vary according to ethnic diversity (14,15,16) .…”
mentioning
confidence: 99%